Stimulation of the bronchus-associated lymphoid tissue of goats and its effect on in vitro colonization by Pasteurella haemolytica - Abdul Wahid, Mohd Effendy; Saad, Mohd Zamri; Mat Amin, Maswati; M. S., Ismail; Samad, Mohd Jamil (Elsevier Science Publishers, 1998)
Twenty goats of about 7 months of age were divided into five groups. The goats in groups 1 and 2 were exposed once, using an intranasal spray to 2 ml of an inoculum containing 106 colony-forming units/ml of living or dead Pasteurella haemolytica A2, respectively. The goats in groups 3 and 4 were similarly exposed twice at a 2-week interval. Group 5 was the untreated control. The number and size of the bronchus-associated lymphoid tissue (BALT) in goats exposed twice to either living or dead organisms were significantly (p>0.05) increased compared with those exposed once and with the unexposed control. In vitro colonization by living P. haemolytica A2 onto the lung tissue in which the BALT had been stimulated by two exposures of either living or dead organisms was significantly (p>0.05) reduced. The study indicates that stimulation of the respiratory mucosal immunity may prevent P. haemolytica A2 infection.